Spontaneous Neck Hematoma in a Patient with Fibromuscular Dysplasia: A Case Report and a Review of the Literature - Oded Cohen; Moshe Yehuda; Meital Adi; Yonatan Lahav; Doron Halperin (Case Reports in Otolaryngology)
Background. Fibromuscular dysplasia (FMD) is a vascular disease that may present as aneurysms in the cervical arteries. Spontaneous neck hematoma is a rare life threatening medical condition. This is the first report of neck hematoma in a patient with FMD. Methods and Results. We present a case of a 69-year-old woman, with diagnosed cervical FMD and a 3-day history of sore throat and neck pain, who presented with enlarging neck hematoma. No active bleeding was noticed on CT angiography, airway was not compromised, and patient was managed conservatively. Next day, invasive angiography was performed, and no bleeding vessel was demonstrated. Patient has improved and was discharged after 5 days of hospitalization. We have discussed the different etiology of this condition, focusing on systemic vascular diseases. Conclusion. Complaint of neck pain in a patient with a FMD should raise suspicion for possible neck hematoma. Conversely, spontaneous neck hematoma without clear etiology should raise suspicion for a systemic vascular disease.